Relationship Between Gestalt and Usability Heuristics in Mobile Device Interfaces - Ripalda, Daniel (2021)
While usability heuristics are universal concepts, visual references for using them in an application are limited, contradictory, and sometimes confusing, especially for novice developers. The present work has linked Nielsen’s heuristics with Gestalt principles, which are the foundation of human perception, developed from psychology, and which have been used in art, design, and architecture, to understand how different visual stimulus can be interpreted by the human being. The heuristics, Match between system and the real world, Recognition rather than recall and Aesthetic and minimalistic design, have been linked with the Gestalt principles of Similarity, Proximity, Common direction, and Simplicity. This link is possible because Gestalt principles have certain conceptual similarities with usability heuristics, in addition to the fact that these fundamentals were identified in some mobile interfaces and are related to specific interactions. This work provides theoretical guidelines, visual references and practical examples on the use of some graphic components that are regularly used in mobile interfaces, such as buttons, menus, and sections; Besides, information is provided regarding how these visual components affect certain usability interactions such as learnability, efficiency, memorability, and usefulness.